Investigation on Abrasive Water Jet Machining of Al-Al2O3 MMC - Bhanudas Bachchhav (International Journal of Industrial Engineering and Production Research, 2021)
The present work aims to investigate Abrasive Water Jet Machining parameters for machining of Al-Al2O3 Metal Matrix Composite. Plan of experiments, based on Taguchi’s analysis technique were performed using L9 orthogonal array. A correlation was established between concentration of Al2O3, Stand-off distance, pressure and Transverse feed with Metal Removal Rate, Surface Roughness, Over-cut and Taper angle by regression analysis. On the basis of experimental results and S/N ratio analysis, ranking of the parameters has been done. The analysis of variance (ANOVA) has been used to find out the impact of individual parameters on response parameters. Al2O3 concentration plays a very significant role in determination of MRR and surface roughness. Also overcut is largely influenced by stand off distance. Furthermore,  multi-objective optimization can be carried out using advanced optimization techniques.  This work helped to generate technical database for industrial applications of MMC.